Adherence to physical activity in young people with Type 1 diabetes - Bernardini, A.L.; Vanelli, M.; Chiari, et al., G. (Acta Biomedica Atenei Parmensis, 2004)
Regular physical activity plays a key role in the management of children and adolescents with Type 1 diabetes mellitus but it is not considered as a treatment for diabetes. Aim of this study was to investigate time spent exercising, adherence to the programme for a safe exercise and ability of young people with diabetes to take appropriate measures to reduce potential risks. Ninety one Type 1 diabetes mellitus young people (aged from 10 to 18 years, duration of diabetes longer than 6 months) without associated chronic diseases were randomly enrolled in the study. Age, sex, weight, height, BMI, duration of disease, mean HbA1c value over preceding 6 months have been collected. The time weekly spent for physical activity, the type of exercise usually performed, the measures taken to reduce exercise risks have been collected by a structured questionnaire. BMI was 21.6±3.05 in the boys and 21.3±3.63 in the girls. All patients spent exercising 438±221 minutes/week. Boys exercised 71 minutes longer than girls in competitive sports. Children exercising less than 60 minutes weekly showed a mean HbA1c level (8,9±05%) higher than that found in children exercising 120-360 minutes (8,3±0.4 %; p=0.002) or 360-480 minutes (8,0±0.6 %; p< 0.01) weekly. Children attending a competitive sport (at least 360 min per week) had a better glycemic control (HbA1c=7,39±0.6 %; p=0.03) than other active peers. Fifty percent of patients reported to monitor blood glucose levels during exercise; 32 % changed insulin dose according to blood glucose levels; 60 % usually added carbohydrate-based foods before (35%), during (15%) or after (10%) exercise. Hypoglycemic episodes (37.7%) were reported more frequently than hyperglycemic ones (p=0.024), but only twelve percent of them were symptomatic and appeared 30 minutes to 2 hours after the end of exercise. These results must encourage health care professionals to review regularly the ability of their patients in managing physical activity and to check their adherence to the program for a safe exercise.